2021
DOI: 10.1002/adem.202101027
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Bionic Porous Polyetherimide Structure by an In Situ Foaming Fused Deposition Modeling Process

Abstract: A wide variety of organisms in nature have excellent structures, which are far superior to artificial machinery. [1] Inspired by nature, the structural characteristics of biological systems were mimicked to design similar new bionic materials, [2,3] to obtain more reliable, efficient, and intelligent material. [4] Porous structure was a prevalent structure in many organisms in nature, such as leaves, [5] trees, and other plants, whose cell structure enhanced fluid transport and adsorption in plant. Porous stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…For the preparation of foamed samples, the PEI filaments were placed in the autoclave at 60 °C after drying at 150 °C for 4 h. According to our previous research, the adsorption and desorption rates of CO 2 in PEI are slow. [ 46 ] To achieve the adsorption equilibrium [ 23 ] and high gas content, [ 23 ] in the following 48 h step, the filaments were saturated with compressed CO 2 at 8 MPa. After saturation, PEI filaments were taken out and placed for 8–240 h for desorption before printing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the preparation of foamed samples, the PEI filaments were placed in the autoclave at 60 °C after drying at 150 °C for 4 h. According to our previous research, the adsorption and desorption rates of CO 2 in PEI are slow. [ 46 ] To achieve the adsorption equilibrium [ 23 ] and high gas content, [ 23 ] in the following 48 h step, the filaments were saturated with compressed CO 2 at 8 MPa. After saturation, PEI filaments were taken out and placed for 8–240 h for desorption before printing.…”
Section: Methodsmentioning
confidence: 99%
“…After saturation, PEI filaments were taken out and placed for 8–240 h for desorption before printing. The desorption rate of CO 2 in PEI material is very low, [ 46 ] it can meet the requirement of long‐time printing of parts. Therefore, the influence of gas content on foam morphology during the long 8–240 h desorption process was studied, while the unfoamed samples were obtained by printing directly after drying without saturation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, PEI was used for MEF to prepare porous fibers, demonstrating its excellent foaming behavior. Afterward, Zhou et al [ 126 ] used PEI for micro-extrusion foam stacking to prepare porous parts. Research showed that as the saturation pressure decreased, desorption time was prolonged, nozzle temperature increased, cell size gradually increased, and cell density gradually decreased.…”
Section: Mef For Porous Partsmentioning
confidence: 99%
“…( B ) Software slicing to determine the printing path. ( C ) The physical object obtained by micro-extrusion foam stacking, honeycomb, ( D ) grid scaffold (un-foamed), ( E ) grid scaffold (foamed), ( F ) triangle scaffold, ( G ) hexagonal scaffold, ( H ) bone, ( I ) loofah, ( J ) bamboo, and ( K ) leaf [ 126 ].…”
Section: Figurementioning
confidence: 99%